Effect of cooking on nutrient composition and anticancer indoles of the marine whelk Dicathais orbita – Can it be another high-value seafood product?. (15th November 2018) - Nongmaithem, Bijayalakshmi Devi; Mouatt, Peter; Eichinger, Yvonne; Savins, Dale; Benkendorff, Kirsten
Highlights: Dicathais orbita is an under utilised marine whelk with functional food potential. The raw and cooked meat has a high protein content with essential amino acids. The low lipid content is dominated by polyunsaturated fatty acids. It produces anticancer brominated indoles that can be retained after boiling. Abstract: The Australian marine mollusc Dicathais orbita has been identified as a functional food with potential for use in the prevention of colon cancer. This study investigated the effect of cooking on the biochemical profile of the edible flesh and extracts containing anticancer brominated indoles. The whelk flesh was high in protein (>75 mg/100 mg dry weight) and there was a significant increase in protein and amino acids after cooking, associated with a loss of moisture and lipids. The flesh also has a high proportion of polyunsaturated fatty acids (>49%), with omega-3:omega-6 around 1. The flesh contains unusually high levels of Docosapentaenoic acid and over 1000 mg/100 g serve of Eicosapentaenoic acid and Docosahexaenoic acid. Cooking resulted in a quantitative decrease in the bioactive compounds, however the main anticancer compound 6-bromoisatin can be retained after boiling. This provides evidence that cooking does not negatively impact the functional food properties of these muricids whelks.